Leopard distribution in relation to human pressures and prey resources in North Khorasan province, Iran - Sanei, Arezoo; Gordmardi, Eskandar; Jafari, Behrouz; Absalan, Hossein; Hussin, Mohamed Zakaria (Faculty of Forestry, Universiti Putra Malaysia, 2013)
The study aimed at identifying leopard-livestock conflict hotspots in the Khorasan Province for leopard conservation and management programs. Camera trappings, tracking (i.e. footprints and faeces), systematic interviews with local communities were used. The most suitable leopard habitats in the province are found in the southern portion of Maneh and Samalghan, Bojnourd, and the northern parts of Jajarm and Esfarayen Townships. Various species of leopard, wolf, wild boar and Indian crested porcupine were found. Leopards were found to be responsible for 10.6 % of the total conflict hotspots. Complaints from the local communities were mostly with regards to damages rendered by wild boar and porcupines, and livestock depredation by wolves. Local community awareness about compensation programs currently conducted by the Department of Environment Office and the introduction of livestock insurance regulations might effectively reduce and prevent leopard revenge killings in the region.